Africa agriculture trade monitor 2020 - Bouët, Antoine; Odjo, Sunday P.; Zaki, Chahir (International Food Policy Research Institute, 2020)
The 2020 Africa Agriculture Trade Monitor, the third in this series of flagship reports, presents an overview of trade in agriculture products in Africa and highlights the main impediments that affect intra- and extra-African trade. This year’s report includes chapters focusing on intra-Africa trade integration for agricultural products, including the role of nontariff measures, and on the competitiveness of African value chains that are crucial for food security (cereals, sugar, vegetable oils). The importance and measurement of informal cross-border trade for agricultural products is also examined. The final chapter looks at regional integration experiences in Southern Africa, with a focus on the Southern Africa Development Community. The report offers policy recommendations for improving agricultural exports performance, especially in the context of the unprecedented uncertainty the world is facing with the COVID-19 pandemic.